The abanico plot: visualising chronometric data with individual standard errors - Dietze, Michael; Kreutzer, Sebastian; Burow, Christoph; Fuchs, Margret C.; Fischer, Manfred; Schmidt, Christoph (Quaternary geochronology, 2016)
Numerical dating methods in Quaternary science are faced with the need to adequately visualise data consisting of estimates that have differing standard errors. Recent approaches either focus on the display of age frequency distributions that ignore the standard errors or on radial plots, that support comparisons between estimates allowing for their differing precisions, but without giving an explicit picture of the age frequency distribution. Hence, visualising both aspects requires at least two plots. Here, an alternative is introduced: The abanico plot. It combines both aspects and therefore allows comprehensive presentation of chronometric data with individual standard errors. It extends the radial plot by a kernel density estimate plot, histogram or dot plot and contains elements that link both plot types. As part of the R package “Luminescence” (version ⩾0.4.5), the abanico plot is designed as the final part of a comprehensive analysis chain of luminescence data but is open to a wide range of other Quaternary dating communities, as illustrated by several examples.